New Cu(II), Cu(I) and Ag(I) Complexes of Phenoxy-Ketimine Schiff Base Ligands: Synthesis, Structures and Antibacterial Activity - Miriam Caviglia; Zhenzhen Li; Carlo Santini; Jo’ Del Gobbo; Cristina Cimarelli; Miao Du; Alessandro Dolmella; Maura Pellei (Molecules)
Two phenoxy-ketimines ligands, 2-(1-(benzylimino)ethyl)phenol (HLBSMe) and 2-((benzylimino)(phenyl)methyl)phenol (HLBSPh), were synthesized and used as supporting ligands of new copper(II), copper(I), and silver(I) complexes. In order to confer different solubility properties to the metal complexes and to stabilize Cu and Ag in their +1 oxidation state, the lipophilic triphenylphosphine (PPh3) and the hydrophilic 1,3,5-triaza-7-phosphaadamantane (PTA) were selected as co-ligands in the syntheses of the Cu(I) and Ag(I) complexes. All compounds were characterized by CHN analysis, NMR, FT-IR spectroscopy, and electrospray ionization mass spectrometry (ESI-MS); the molecular structure of the copper(II) complex [Cu(LBSPh)2] was also determined by single-crystal X-ray diffraction. Finally, the antibacterial activity of the metal complexes, the Schiff base ligands and phosphane co-ligands, were assessed by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against Gram-negative (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus).